Utilizing optical conjugate plane to enhance 3D focusing and forming shapes behind turbid media - Tran, Vinh (2020)
Inner diffraction phenomenon is known as the major obstacle of light transmission through scattering media such as ground glasses, skin or biological tissue. Recently, the most effective and convenient solution is wave-front shaping technique which modulates the field profile of incident light by using a spatial light modulator (SLM). For practical and advanced biomedical applications, requirement of speedy response, high accuracy and large energy delivery are necessary. In our previous work, we presented a wave-front shaping technique and utilized optical memory effect for swiftly drawing various 2 dimensional (2D) shapes or contours through a scattering medium without any mechanical movement. However, with process of scanning angle phase profile and shifting phase pattern on SLM, the accuracy and beam energy utilization are still very much restricted. Here, we present an exceeding improvement from previous technique by establishing optical conjugate planes between SLM and scattering medium surface, which is also known as 4F system. With only one phase profile for creating a focus spot behind scattering medium, we are able to swiftly move focus spot in 3D space or draw any 3D contours through turbid medium without scanning or shifting process. The new approach allows us to deliver laser energy through a scattering medium to any spot within 3D memory effect space with very fast response, high accuracy and more importantly, fully utilized laser beam energy. Our approach demonstrates a practical method to control light through scattering media for prominent applications such as opto-genetic excitation, minimal invasive laser surgery and other related fields.